In vitro Studies of Interaction Between Dexamethasone and NSAIDS by Using RP-High Performance Liquid Chromatography. Issue 1 (2nd January 2018) - Tahir, Sobia; Yasmeen, Kousar; Haroon, Urooj; Tahiri, Iftikhar Ahmed; Versiani, Muhammad Ali; Muhammad, Haji; Jahangir, Sajid; Zuberi, Hashim; Bin Asif, Safi Asim
Abstract: Non-steroidal anti-inflammatory drugs (NSAIDS) are commonly used because of their remarkable cure over mild and moderate pain including osteoarthritis and rheumatoid arthritis. Medical doctors commonly prescribe steroidal drugs in combination with the NSAID's therefore we have developed a method to evaluate the percent availability of these two classes of drugs and analyzed their possible interactions. The proposed method is validated according to the International Conference on Harmonization (ICH) guide lines on RP-HPLC (Reverse Phase High Performance Liquid Chromatography). A good chromatographic separation was achieved using a mobile phase containing methanol-water (80:20 v/v) at pH = 3.2 with a flow rate of 1.0 mL/min (detection at 265 nm with a UV-vis detector). The in-vitro interaction study was conducted at physiological conditions (i.e. temperature 37°C and stomach pH = 3.2). The method provided a very good percent recovery of different molecules. The percent recovery of Piroxicam, Naproxen sodium, Flurbiprofen and Ibuprofen are 100.539, 100.373, 99.683 and 100.840 respectively. The results indicated that percent availability of all NSAIDs and dexamethasone reduced during the time interval 2.5 h which is likely due to the formation of charge transfer complexes. We can conclude that simultaneous administration of these drugs may alter their bio-availability.